Mild chronic kidney disease is associated with cognitive function in patients presenting at a memory clinic. (4th November 2014) - Romijn, Marloes D.M.; van Marum, Rob J.; Emmelot‐Vonk, Mariëlle H.; Verhaar, Harald J.J.; Koek, Huiberdina L.
<x xml:space="preserve">Abstract</x> Objective In dialysis‐dependent and severe chronic kidney disease (CKD) patients, cognitive impairment is found in 16–29%. In community‐dwelling population without dementia mixed results have been observed. We investigated the relationship between renal function and cognition in patients from a memory clinic. Methods We performed a cross‐sectional study of consecutive patients from a memory clinic between 2005 and 2009. Renal function was estimated with the Modification of Diet in Renal Diseases (MDRD) and Cockcroft‐Gault (CG) formulas, and categorized into ordinal groups: reference ≥60 ml/min/1.73 m2, mild CKD 45–59 ml/min/1.73 m2 and moderate CKD <45 ml/min/1.73 m2. Cognitive function was dichotomized (Mini‐Mental State Examination (MMSE) ≥24 vs. <24). We performed multiple logistic regression analyses with adjustment for potential confounders. Results The cohort comprised 581 patients (mean age 77 ± 10 years). With the MDRD, there were 74 (12%) cases with moderate CKD and 108 (18%) with mild CKD. With the CG, these prevalences were 144 (30%) and 130 (27%). In mild CKD patients, a significant relationship was found between cognitive function and CKD according to the MDRD‐formula [adjusted OR 2.10; 95%CI 1.09–4.05]. In moderate CKD patients, no significant adjusted associations were found. In patients without dementia, significant adjusted associations were found between CKD and MMSE (MDRD: mild CKD [OR 5.09; 95%CI 1.17–22.14] and moderate CKD [OR 5.03; 95%CI 1.10–22.98]; CG: mild CKD [OR 6.16; 95%CI 1.17–32.50] and moderate CKD [OR 5.60; 95%CI 1.01–30.91]). Conclusion This study showed a significant association between mild CKD and impaired cognitive function in patients from a memory clinic, especially in patients without dementia. Copyright © 2014 John Wiley & Sons, Ltd.